Fecal calprotectin as a noninvasive test to predict deep remission in patients with ulcerative colitis - Malvão, Ludimilla dos Reis (Medicine (Baltimore), 2021)
Mucosal healing (MH) has become a major target in the management of ulcerative colitis (UC). Because repeat endoscopy is expensive and invasive, we aimed to evaluate fecal calprotectin (FC) as an alternative marker to predict MH in UC. Eighty patients with UC in clinical remission were consecutively included in a prospective observational study. FC was measured using a quantitative enzyme-linked immunosorbent assay. The colonic mucosa was assessed for endoscopic and histological measures of inflammatory status. Endoscopic and histological remission were defined according to the Mayo endoscopic subscore (MES) and Geboes score (GS), respectively. Deep remission was defined as a combination of the MES and GS. FC performance and cutoff values for identifying MH and deep remission were determined using contingency tables and receiver operator characteristic (ROC) and area under the curve (AUC) analysis. The median FC concentration in patients who met the criteria for deep remission (MES ≤1 and GS < 3.1) was 65.5 μg/g, while that in patients with disease activity was 389.6 μg/g (P = .025). A FC cutoff value of 100 μg/g, determined by the ROC analysis, resulted in sensitivity and specificity of 91.7% and 57.1%, respectively, for histological remission, and 82.4% and 60.9%, respectively, for deep mucosal remission. Positive correlations were detected between FC concentrations with the histologic (CC: 0.435; P < .001) and the combined endoscopic and histologic (CC: 0.413; P < .001) scores. FC can be used confidently as a noninvasive biomarker to predict deep remission in patients with UC in clinical remission when concentrations are below 100 μg/g.